Cuidados de Enfermería para la prevención de hemorragias posparto en pacientes Ginecológicas de la sala de Maternidad del Hospital León Becerra de Milagro, durante agosto-octubre 2018 - Lumbi Soria, Jazmín Elizabeth (2019)
Postpartum hemorrhages, mostly caused by uterine atony, is the most frequent cause of preventable maternal mortality worldwide, and the second most important cause of maternal death in Ecuador, when it can not be adequately controlled or treated, can quickly lead to hypovolemic shock and in the worst cases death. The nurse as part of the health team is in charge of providing direct care to the mother and her child during childbirth and the puerperium, in addition the nursing staff is a key element for the prevention and timely detection of postpartum hemorrhage and can provide the First care in the management of this obstetric complication. The objective of the research was to determine what nursing care is for the prevention of postpartum haemorrhage in gynecological patients in the maternity ward of the Leon Becerra Hospital in Milagro. For this purpose, a cross-sectional study was carried out by means of previously prepared surveys. which was taken as sample a total of 14 people; the same ones that were surveyed, of which 6 are nursing professionals and 8 nursing auxiliaries were included because they also provide direct care due to the lack of personnel in the hospital. At the conclusion of the investigation, it was obtained that there is a deficit of knowledge about the risk factors, active management of the third stage of delivery and nursing care that should be given to gynecological patients; both on the part of the nursing staff, as well as of the nursing assistants, resulting in that the nurses have a knowledge of 40% to 60% that would be an average assessment and the nursing assistants have low knowledge of 0% to 30%; In addition, the patients were educated about the risk factors that produce postpartum hemorrhages through the talks included in the educational program. Key Words: Postpartum hemorrhage, uterine atony, nursing staff, nursing care.